Acceptance sent through email; is the postal rule applicable? - Defossez, Delphine (Law, State and Telecommunications Review, 2019)
Purpose ”“ This paper focuses on the application of the postal rule to email, due to the controversy surrounding the application of the “instantaneous” test to emails. Methodology/approach/design ”“ This article analyses standards and literature on the formation of contract under English law. Findings ”“ Although the postal rule is an invention of its time, this rule could still play a role regarding emails. Indeed, due to the difficulties in applying the “instantaneous” test to emails, emails would still be subject to the postal rule. Of course, the postal rule in its current form is no more fitting the reality. However, the benefits that such rule provides should not be lost, instead a new rule could be drafted based on the postal rule. Practical implications ”“ This article discusses the possible improvements to the already existing framework. Originality/value ”“ This paper analyses the use of the postal rule to electronic contracts in the UK, a topic that is not much researched but could have great importance when doing electronic business.